The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fphar.2023.1195146
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicines and natural products targeting immune cells in the treatment of metabolic-related fatty liver disease

Abstract: MAFLD stands for metabolic-related fatty liver disease, which is a prevalent liver disease affecting one-third of adults worldwide, and is strongly associated with obesity, hyperlipidemia, and type 2 diabetes. It encompasses a broad spectrum of conditions ranging from simple liver fat accumulation to advanced stages like chronic inflammation, tissue damage, fibrosis, cirrhosis, and even hepatocellular carcinoma. With limited approved drugs for MAFLD, identifying promising drug targets and developing effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 208 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…At present, increasing evidence has shown that alcohol-induced abnormity can be regulated by autophagy ( Li, Ouyang & Zhu, 2023 ). Autophagy is a critical self-protection and survival mechanism of eukaryotic cells that exerts a protective role in ALD by scavenging damaged mitochondria ( Thomes et al, 2015 ), accumulated LDs ( Lin et al, 2013 ; Schulze et al, 2017 ), and protein polymers ( Bonilla et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, increasing evidence has shown that alcohol-induced abnormity can be regulated by autophagy ( Li, Ouyang & Zhu, 2023 ). Autophagy is a critical self-protection and survival mechanism of eukaryotic cells that exerts a protective role in ALD by scavenging damaged mitochondria ( Thomes et al, 2015 ), accumulated LDs ( Lin et al, 2013 ; Schulze et al, 2017 ), and protein polymers ( Bonilla et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors, such as oxidative stress-induced lipotoxicity and cellular senescence, contribute to the pathogenesis and progression of MAFLD ( 12 ). Additionally, inflammatory responses accelerate the development of MAFLD ( 13 ). A study reported that several components of traditional Chinese herbal medicine could inhibit liver inflammation and alleviate liver damage ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inflammatory responses accelerate the development of MAFLD ( 13 ). A study reported that several components of traditional Chinese herbal medicine could inhibit liver inflammation and alleviate liver damage ( 13 ). Therefore, supplementing the antioxidant or anti-inflammatory nutrients might have similar effects.…”
Section: Introductionmentioning
confidence: 99%